Evaluación a Académicos Universitarios en Francia. Interpretación de Distancias con un Caso Mexicano - Lastra B., Rosalía S. (Acta Universitaria, 2008)
A controversial university issue is the way that the public sector promotes the recognition of some of the prominent efforts of academia, through programs of merit pay, consistent in the verification of “academic productivity”. In search of the experience in countries with renowned educational systems, the exploration of a French case was undertaken. Although in France these programs are not in operation, the elements found regarding the academic classification system may allow for established deliberations on the different challenges faced by a consolidated academic community and those of another in the process of consolidation, considering their respective contextual, structural and attitudinal fundamentals. Their convergence is focused on the search for “excellence” and in that concern to determine under what circumstances and with what decisions it may be possible to improve results. After the generalities of the French system, deliberations are presented on the disparities found with the Mexican group upon the evaluation for the entrance of new academics, the importance of the multi-functional academian, the types of stimuli and institutional considerations.